2019
DOI: 10.1007/s10802-019-00609-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Parent and Child Report on the Screen for Child Anxiety-Related Emotional Disorders (SCARED): Implications for Investigations of Social Anxiety in Adolescents

Abstract: Social anxiety typically emerges by adolescence and is one of the most common anxiety disorders. Many clinicians and researchers utilize the Screen for Child Anxiety Related Disorders (SCARED) to quantify anxiety symptoms, including social anxiety, throughout childhood and adolescence. The SCARED can be administered to both children and their parents, though reports from each informant tend to only moderately correlate. Here, we investigated parent-child concordance on the SCARED in a sample of adolescents (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…For children, overall SCARED scores ranged from 1–30 ( M = 9.59, SD = 7.54), social anxiety scores ranged from 0–12 ( M = 2.78, SD = 2.94), and generalized anxiety scores ranged from 0–16 ( M = 3.00, SD = 3.40). These scores are in line with past studies of community samples (e.g., Bowers et al., 2020; Rappaport, Pagliaccio, Pine, Klein, & Jarcho, 2017). Given that the children in our sample had not received official clinical diagnoses and were recruited via community sampling, we included the full sample in final analyses.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…For children, overall SCARED scores ranged from 1–30 ( M = 9.59, SD = 7.54), social anxiety scores ranged from 0–12 ( M = 2.78, SD = 2.94), and generalized anxiety scores ranged from 0–16 ( M = 3.00, SD = 3.40). These scores are in line with past studies of community samples (e.g., Bowers et al., 2020; Rappaport, Pagliaccio, Pine, Klein, & Jarcho, 2017). Given that the children in our sample had not received official clinical diagnoses and were recruited via community sampling, we included the full sample in final analyses.…”
Section: Methodssupporting
confidence: 90%
“…One limitation of the current work is that we only included one assessment of social anxiety in each age group, and that social anxiety was measured with two different scales and different report types (parent for child and self for adult), limiting direct comparisons. Different measurements may be responsible for the relatively higher social anxiety scores (compared to conventional cut‐offs) and larger range in our adult versus child samples, particularly given that parents tend to report lower levels of social anxiety in their children than children themselves do (Bowers et al., 2020; Rappaport et al., 2017). The levels of social anxiety in our college student sample may also reflect real increases in college student anxiety in the past decades (e.g., Booth, Sharma, & Leader, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Studies showed children couldget fear and avoidance behavior at an early age through observational learning and modeling. It was reported that there might be a difference between the levels of anxiety observed by the family and reported by the child, and this provides different and valuable information about anxiety 15 . Data from epidemiological and family studies reported that anxiety disorders were familial, and mother anxiety predicted child anxiety when the effects of upbringing were evaluated 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Eighty-three (68.60%) of the parents were working as a physician. The mean age of the children was 11.88 ± 3.21(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and 62(51.24%) children were boys. Mean Beck Anxiety Inventory score was found as 16.56 ± 13.60 and median value was 13 (range 0-52).…”
mentioning
confidence: 99%
“…Total anxiety scores were the primary outcome of interest. In order to combine information from multiple informants while also accounting for differences in how parents and children rate anxiety symptoms (Bowers et al, 2020), total anxiety scores were computed separately for parent and child, Z-transformed, and then averaged together to form an anxiety composite score for analyses (for separate regression results involving child-reported or parent-reported anxiety, see Supplementary Tables S1-S4).…”
Section: Methodsmentioning
confidence: 99%